Induction of mammary gland tumor in female Sprague-Dawley rats with LA7 cells - Abbasalipourkabirreh, Roghayeh; Dehghan, Arash; Salehzadeh, Aref; Shamsabadi, Fatemeh; Abdullah, Rasedee (Academic Journals, 2010)
The current methods for tumor induction in breast cancer research animal models are time-consuming, hazardous, expensive, sometimes irreproducible and inconvenient. We successfully developed a new, simple and cost-effective method in developing solid mammary gland tumor in female Sprague-Dawley rat using LA7 rat mammary tumor cells. Tumors developed in 7- 8 weeks old rats within 6 to 8 days of subcutaneous injection of LA7 cells into the mammary gland pad. Tumor size increased exponentially for four weeks. Histopathology examination confirmed that the induced tumors were adenocarcinomas. Evaluation of blood enzymes showed significantly higher (P < 0.005) serum alkaline phosphatase (ALP) and lactate dehydrogenase (LDH) in tumor-bearing than in normal rats. This LA7 cell-induced rat mammary gland tumor model may be useful for studies in breast cancer drug or nutraceutical research and development.